CURRICULUMM AS A DYNAMIC SYSTEM - Budiyanto, Setyo Mei (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The main target and aims of this writing are: to show that curriculum is a dynamic system, therefore, it can be developed to follow the era progressing, the need and level of our students. It is to show that curriculum is excellent and accurate guiding for the successfull of teaching learning process. Better we make curriculum will be better and greater the result of education. Above all, character building is the most important target of curriculum and education. There are a lot of aspects in curriculum that should be learned carefully and seriously. Therfore, the government/Education Minister should be smart in making curriculum design that is good, accurate, and suitable for our students, if not, they will make a big mistake in taking decision, so the impacts will be scarry for the future generation.